Unpleasant Surprises : Sovereign Default Determinants and Prospects - Bandiera, Luca (2012)
This paper uses model averaging techniques to identify robust predictors of sovereign default episodes on a pooled database for 46 emerging economies over the period 1980-2004. Sovereign default episodes are defined according to Standard & Poor s or by non-concessional International Monetary Fund loans in excess of 100 percent of the country s quota. The authors find that, in addition to the level of indebtedness, the quality of policies and institutions is the best predictor of default episodes in emerging market countries with relatively low levels of external debt. For emerging market countries with a higher level of debt, macroeconomic stability plays a robust role in explaining differences in default probabilities. The paper provides evidence that model averaging can improve out-of-sample prediction of sovereign defaults, and draws policy conclusions for the current crisis based on the results.